2019
DOI: 10.1177/1078155219849275
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a topical moisturizing preparation for regorafenib-related hand-foot skin reaction

Abstract: Objective Application of topical moisturizing preparations is important for the prevention and palliation of hand-foot skin reaction induced by multi-kinase inhibitor. Application adherence of topical moisturizing preparations in clinical practice has rarely been reported. This study investigated the factors affecting adherence to the application of topical moisturizing preparations in patients administered regorafenib. Methods The subjects were patients administered regorafenib ( n = 118). Consumption of a ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Previously, we retrospectively investigated adherence to topical moisturizer in patients receiving regorafenib. 10 In that study, 36% of the patients had poor adherence, and used <6 FTU/day (3 g/day), when topical moisturizer was prescribed to cover both hands and feet. Kobayashi et al also reported that topical moisturizer use in patients receiving sorafenib greatly varied.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previously, we retrospectively investigated adherence to topical moisturizer in patients receiving regorafenib. 10 In that study, 36% of the patients had poor adherence, and used <6 FTU/day (3 g/day), when topical moisturizer was prescribed to cover both hands and feet. Kobayashi et al also reported that topical moisturizer use in patients receiving sorafenib greatly varied.…”
Section: Discussionmentioning
confidence: 94%
“…Employment status was found to affect adherence in our previous survey. 10 However, we did not analyze the employment status of our study patients. Future studies are required to verify the effectiveness of pharmaceutical instructional video for adherence to topical moisturizer use in a randomized manner or after adjusting for patient background.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The 7 trials were published between 2010 and 2020 and had sample sizes ranging from 32 to 871, with a total of 1387 participants. Among the 7 trials, 4 were RCTs, 10,11,18,20 1 was a prospective cohort study, 18 and 2 were retrospective cohort studies 17,21 . All trials recruited patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…All trials recruited patients with cancer. Four trials enrolled patients newly starting with chemotherapy, 10,11,19,20 1 trial enrolled patients who were already receiving chemotherapy and had developed first-grade HFS, 18 and 2 trials enrolled patients receiving chemotherapy retrospectively 17,21 . All included trials used urea cream as the prevention or treatment strategy for HFS.…”
Section: Resultsmentioning
confidence: 99%